MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI PERMAINAN PUZZLE PADA ANAK USIA DINI - Rima (GHULAMUNA: JOURNAL OF EARLY CHILDHOOD EDUCATION, 2024)
This research aims to improve fine motor skills in Kasih Ibu PAUD children. The subjects in this research were 15 class A students. Where the researcher made initial observations on the 15 students. The research procedure uses Classroom Action Research , the researcher collects data by observation and documentation. The results obtained from the first cycle test are 53%, including in the incomplete value category, while the second cycle test results are 80%, including in the complete value category. So it can be concluded that using the Puzzle playing method can improve children's fine motor skills very well.